2015
DOI: 10.1186/s12903-015-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and comparative analysis of discriminative validity of the Scale of Oral Health Outcomes for Five-Year-Old Children (SOHO-5) and the Early Childhood Oral Health Impact Scale (ECOHIS) for dental caries

Abstract: BackgroundThe perceptions of parents and children regarding oral health are useful to oral public health and clinical practice in pediatric dentistry. The primary aim of the present study was to evaluate the correlation between the total and item scores of the Scale of Oral Health Outcomes for Five-Year-Old Children (SOHO-5) (parental version and child’s self-reports) and the Early Childhood Oral Health Impact Scale (ECOHIS). Subsequently, the discriminative validity of these assessment tools regarding dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
2
24
1
Order By: Relevance
“…Higher average total SOHO-5c scores expressed that children in this study tended to classify their OHRQoL as more compromised than their parents, and a significant difference was found among parent-child pairs (p = 0.0028). Similar results were found in research conducted with young children [7,8,22], when comparing the total SOHO-5 scores (parents and children's version),…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Higher average total SOHO-5c scores expressed that children in this study tended to classify their OHRQoL as more compromised than their parents, and a significant difference was found among parent-child pairs (p = 0.0028). Similar results were found in research conducted with young children [7,8,22], when comparing the total SOHO-5 scores (parents and children's version),…”
Section: Discussionsupporting
confidence: 88%
“…The values of differences in the items found in this study corresponded to 3.5-21% of the maximum scores and were lower than those found by Brazilian authors [8], which may be explained by the fact that not every 5-6-year-old child age has the same level of cognitive development [3]. A child's perception of his/her oral health is influenced by age, cognitive, and emotional development, as well as by the social context in which he/she is inserted [22].…”
Section: Discussioncontrasting
confidence: 66%
“…However, all the studies cited used a proxy measure (ECOHIS), and most investigations using the SOHO-5 have employed a convenience sample [Abanto et al, 2013[Abanto et al, , 2014Dantas et al, 2015]. Studies using the SOHO-5 with a representative sample have revealed a correlation with the ECOHIS [Fernandes et al, 2015] as well as the negative impact of cavities and increased overjet on OHRQoL [Abanto et al, 2017]. It should be pointed out that the majority of preschool children in Brazil make use of public dental services [Machry et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the index of the early childhood oral health impact scale (ECOHIS) (4), which is an appropriate and successful questionnaire in this field (7)(8)(9). Jabarifar et al examined the validity of Farsi-ECOHIS and concluded that this index is valid and reliable for assessing OHRQoL in Persian-speaking parents of preschool children with 2 -5 years old (9).…”
Section: Introductionmentioning
confidence: 99%